(untitled) (Journal of the College of Basic Education, 2024)
In this study, crude aqueous and ethanol extracts was prepared from Punica granatum seeds and peels, then evaluate the anticancer effects of these extracts on cancer and normal cell lines. Michigan Cancer Foundation-7 (MCF-7) and Ahmed, Murtudha, Jabriyah, 2013 (AMJ13) cancer cell lines and Rat Embryo Fibroblast (REF) normal cell line were used in the in vitro study. Cell line exposure times were estimated after 24, 48, and 72 hours, and normal cell line was calculated after only 72 hours of exposure in a micro titration plate under sterile conditions. Anti-cancer property of Punica granatum extracts on cancer cell lines has been reported and there was not effect on normal cell line. In this work, the MCF-7, AMJ13 and REF cell line were treated with different concentrations of four type of extracts (15.62, 31.25, 62.5, 125, 250 and 500 μg/mL). and the cytotoxic effect of crude extracts was investigated using the microculture tetrazolium test (MTT). The result obtained showed time and concentration dependent inhibition effect; the higher concentrations gave significantly (p<0.05) higher cytotoxic effect at 48 hours of exposure.